2012
DOI: 10.1002/cncr.27862
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms predict toxicity to neoadjuvant therapy in patients with rectal cancer

Abstract: Background Toxicity from neoadjuvant chemoradiation therapy (NT) increases morbidity and limits therapeutic efficacy in patients with rectal cancer. Our objective was to determine whether specific polymorphisms in genes associated with rectal cancer response to NT correlate with NT-related toxicity. Methods One hundred thirty-two patients with locally advanced rectal cancer were treated with NT followed by surgery. All patients received 5-fluorouracil (5-FU) and radiation (RT), and 80 patients also received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The previously reported association of toxicity with the SNPs of interest was based on an autosomal dominant mode of inheritance, comparing patients with 1 or 2 minor alleles with those with none (7, 8). Therefore, our analysis was performed in the same fashion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The previously reported association of toxicity with the SNPs of interest was based on an autosomal dominant mode of inheritance, comparing patients with 1 or 2 minor alleles with those with none (7, 8). Therefore, our analysis was performed in the same fashion.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA was of good quality, as assessed by spectrophotometry. The SNPs XRCC1 R399Q (rs25487), XPD K751Q (rs13181), and TGFβ1 R25P (rs1800471), identified in previous studies (7, 8), were assessed using iPLEX SNP Genotyping with the MassArray platform (Sequenom, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The T allele has been strongly associated with toxicity in locally advanced rectal cancer patients treated with 5-Fu and radiotherapy. 49 It has also been associated with an increased risk of severe gastrointestinal toxicity in lung cancer patients treated with cisplatin-based chemotherapy, 50 and CRC patients with the C/C genotype experienced less neurotoxicity after adjuvant oxaliplatin. 20 Lee et al 20 further showed that the onset of neurotoxicity was significantly later for patients with the C/C genotype.…”
Section: Discussionmentioning
confidence: 99%